(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2025)
The starting point for this article is the creation of entrepreneurial initiatives carried out in Paraisópolis due to local experiences in the battle against COVID-19. It focuses its analysis specifically on the enterprise Favela Brasil Xpress (FBX). The FBX, a last mile distribution logistic hub served as a basis for the study of how consumption and the circulation of objects managed to put the favela on the map”. It took into consideration two specific actions carried out by FBX: the unblocking of Paraisópolis postcodes in the delivery systems of large retail chains; and the design and implementation of Plus-Code project in Paraisópolis alongside with Google. Methodologically, an ethnographic investigation was developed, with two visits to Paraisópolis (May/2022 – June/2023), in which in-depth interviews were carried out with local residents.